Adoption of Building Information Modelling in Construction: The Case of a Small - to Medium-sized Enterprise - Azarikasmaee, Yasamin (Curtin University, 2017)
This research aims to understand why and how small to medium enterprise (SME) construction companies can effectively utilise Building Information Modelling (BIM). Using an in-depth case study, it focuses on an organisation that used design-build methods within the residential sector. The research demonstrates that many of the enabling foundations of BIM are already in place within this sector and the move towards a collaborative environment can be enabled without the need for disruptive changes.